1996
DOI: 10.1080/01904169609365104
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus nutrition and water stress tolerance in wheat plants

Abstract: The effect of phosphorus (P) nutrition and soil water availability (W) on the growth of wheat (Triticum aestivum L.) plants was studied in two pot experiments. Several levels of P supply were applied once before sowing. Before seedling establishment, the pots were kept near 100% of field capacity (FC). Afterwards, half of the pots were maintained between 60-70% FC. Control pots were kept at 85-95% FC by weighing and watering every two to three days. Several harvest of shoots were done before anthesis. At each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…All of these elements improved dry matter production in both wet and dry conditions (e.g. Rodriguez et al 1996). Silicon is distinct from these elements, as silicon‐induced acceleration of dry matter production in sorghum is observed only when the plants are subjected to drought (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…All of these elements improved dry matter production in both wet and dry conditions (e.g. Rodriguez et al 1996). Silicon is distinct from these elements, as silicon‐induced acceleration of dry matter production in sorghum is observed only when the plants are subjected to drought (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions observed in this study were thoroughly studied in a previous paper (16). Generaly, the final shoot dry weight and P uptake increased with the level of P supply.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that P supply can ameliorate the adverse effects of drought on yield performance in many crops such as wheat [14], barley [15], soybean [5,7,16,17] and cowpea [18]. In these crops, the improvement in seed yield with P supply under different water deficits was associated with an increase in dry matter accumulation [5,7,16], but there is little information about how the increased P supply affects specific shoot traits when subjected to a water deficit.…”
Section: Introductionmentioning
confidence: 99%